PENGEMBANGAN SISTEM MONITORING ALAT PEMADAM API RINGAN (APAR) BERBASIS WEBSITE DENGAN METODE AGILE - Winanti Winanti; Muhammad Raihan; Riyanto Riyanto; Jumiran Jumiran; Nurasiah Nurasiah; Jainuri Jainuri (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2025)
The Light Fire Extinguisher (APAR) Monitoring System at PT. Erje London Chemical in this case known as PT XYZ is currently not integrated. Several problems in APAR management are data that is not well documented, information on the location, condition, and maintenance schedule of APAR is still done manually so that it is difficult to arrange a periodic maintenance schedule. A Monitoring APAR information system is needed in the form of a Website-based application that is able to provide information on APAR in real time and facilitate data access. The system is designed to facilitate monitoring of APAR conditions, facilitate reporting, and ensure that APAR is ready to use. The data collection method is carried out through literature studies from previous research and books and based on the results of interviews with stakeholders. The system is built based on a website and the system development uses the Agile method and testing is carried out using blackbox testing, the results of which are that all features have been tested and the results are all successful. The system that is built provides fast and accurate information that is able to overcome problems that occur, reduce the risk of fire, improve work safety, and support the sustainability of company operations at PT. XYZ. The results of this study indicate that the use of the APAR Monitoring information system can provide benefits in terms of managing safety equipment and compliance with work safety standards.